PENGARUH LIKUIDITAS, PROFITABILITAS, DIVIDEN DAN SIZE DENGAN PERTUMBUHAN LABA SEBAGAI VARIABEL MODERASI - Puspita, Mery Dwilinda; Subardjo, Anang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The stock price is an important factor to be concerned by the investor in doing their investment because the stock price shows the work achievement and firm value. Liquidity, profitability, dividend policy, and firm size are one of the factors which are influences the stock price.The data source of this research is use the secondary data in a form of Annual Report in 2010-2014 of food and Beverages Company in Indonesia Stock Exchange with the sample collection technique is using purposive sampling technique. The quality test is a normality test, classic assumption test which consist of heteroscedasticity test, multicolonearity and autocorrelation. The data analysis technique is a multiple linear regressions analysis and interaction test of Moderated Regressions Analysis. The result of this research shows that earning per share and firm size have significant influence to the stock price. Meanwhile, current ratio and dividend per share does not have any significant influence to the stock price if it moderated by the earnings growth as the moderation variable, it shows that earning per share and firm size have significant influence to the stock price. Meanwhile, the current ratio and fixed dividend per share does not have any influence to the stock price.Keywords: Current Ratio, Earning Per Share, Dividend Per Share, Firm Size, Earning Growth